2000
DOI: 10.1073/pnas.98.1.241
|View full text |Cite
|
Sign up to set email alerts
|

Costimulation via lymphocyte function-associated antigen 1 in the absence of CD28 ligation promotes anergy of naïve CD4+T cells

Abstract: The mechanisms controlling induction of anergy at the level of naïve CD4 ؉ T cells are poorly understood but thought to reflect limited contact with costimulatory molecules during T cell antigen receptor (TCR) ligation. To clarify this question, naïve TCR transgenic CD4 ؉ cells were exposed to specific peptide presented by transfected antigen-presenting cells (APC) expressing MHC class II molecules with defined accessory molecules. Significantly, culturing CD4 ؉ cells with APC expressing MHC II plus peptide al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 45 publications
2
20
1
2
Order By: Relevance
“…Similarly, clustering of T cells with DCs in liquid culture was also impaired, emphasizing the relevance of LFA-1 as a cell-cell adhesion molecule. In addition to this function, more recent studies have suggested an active role of LFA-1 in intracellular signalling, leading to T-cell activation (Zuckerman et al, 1998;Ni et al, 1999;Ragazzo et al, 2001;Perez et al, 2003). To further analyze this feature, we performed mixed lymphocyte reactions with allogeneic DCs.…”
Section: Relevance Of B 2 Integrins For Tcr Signalling and Costimulationmentioning
confidence: 98%
“…Similarly, clustering of T cells with DCs in liquid culture was also impaired, emphasizing the relevance of LFA-1 as a cell-cell adhesion molecule. In addition to this function, more recent studies have suggested an active role of LFA-1 in intracellular signalling, leading to T-cell activation (Zuckerman et al, 1998;Ni et al, 1999;Ragazzo et al, 2001;Perez et al, 2003). To further analyze this feature, we performed mixed lymphocyte reactions with allogeneic DCs.…”
Section: Relevance Of B 2 Integrins For Tcr Signalling and Costimulationmentioning
confidence: 98%
“…While early studies indicated that LFA-1 may behave as a classical costimulatory molecule like CD28, subsequent studies revealed that the contribution of LFA-1 to T cell activation is distinct [43][44][45]. Thus, on naïve CD4 + T cells, CD28 plays a central role in costimulation, synergizing with signals delivered through the antigen specific TCR to stimulate robust T cell activation, proliferation and the production of pro-inflammatory cytokines such as IL-2; on these same cells, costimulation through LFA-1 and the TCR leads not to T cell activation but to anergy [46,47]. On virus specific CD8 + T cells LFA-1/ICAM-1 interactions stabilize cytotoxic T lymphocyte (CTL)/target binding, support CTL proliferation and may also participate in the generation of long-lived memory CTL.…”
Section: The Role Of Lfa-1 In Inflammationmentioning
confidence: 99%
“…cells express high levels of MHC-II, but they lack CD80 and CD86 costimulatory molecules and thus cannot activate Th1 CD4 þ T cells, However, they do induce pulmonary tolerance by triggering the differentiation of regulatory T cells (Tregs) (Ragazzo et al, 2001;Lo et al, 2007;Gereke et al, 2009). Insufficient antigen processing and presentation by APCs may increase the frequency of Tregs, resulting in defects in the maintenance of effective antitumor surveillance (Seliger, 2012).…”
mentioning
confidence: 99%